Morphological investigations on the duodenum in sousliks (Spermophilus Xanthoprymnus) - Özkan, Z. Ender; Timurkaan, Sema; Ilgün, Ramazan (Croatian Natural History Museum, 2009)
In the present study six adult souslik duodenums were fixed in the formaldehyde solution. The trimmed parts were blocked in the paraffin and sectioned in 5 micrometers thick parts. The sections were stained with the methods of Haemotoxylin-Eosin and PAS in the Souslik duodenum, the main mucosal constituents villi intestinales, crypts and goblet cells were prominent. The average heights of the villi intestinales in the duodenum formed 76% of the whole transversal diameter of the first part (I), 82% of the middle part (II) and 65% of the last part (III) near the jejunum. The average height of the villi intestinales in the middle part (II) was 40% and 60% higher than the average heights of the part I and III. The goblet cells were stained by the PAS reaction excessively but Brush border and the duodenal glands were slightly stained by the PAS reaction.
Keywords: Duodenum; Morphology; Souslik